Outcomes of Ventriculoperitoneal Shunt in Patients With Idiopathic Normal-Pressure Hydrocephalus 2 Years After Surgery - Popal, Abdul Malik; Zhu, Zhoule; Guo, Xinxia; Zheng, Zhe; Cai, Chengwei; Jiang, Hongjie; Zhang, Jianmin; Shao, Anwen; Zhu, Junming (Frontiers in Surgery, 2021)
Objective: To evaluate the outcomes and prognostic factors of ventriculoperitoneal shunts (VP-shunts) in patients with idiopathic normal-pressure hydrocephalus (iNPH) at 6 months and 2 years after surgery. Method: We retrospectively analyzed 68 patients admitted to our institute and diagnosed with probable iNPH from January 2017 to March 2021. All patients underwent VP-shunt surgery with a programmable valve, and their outcomes were assessed via the Krauss index and modified Rankin scale (mRS) at 6 months and 2 years postsurgery. Univariate and multivariate regression analysis was performed to identify the prognostic factors. Results: The mean age of the patients was 71.1 ± 8.4 (mean ± standard deviation) years. On the Krauss improvement index, 6-month follow-up results were available for 68 patients. Of these patients, 91.2% experienced attenuation of their preoperative symptoms, with a mean Krauss index of 0.58 ± 0.27, and 48 patients (70.6%) had a Krauss index ≥0.5. Two-year follow-up results were available for 33 patients; 90.9% of them had sustained improvement, with a Krauss index of 0.54 ± 0.31, and 21 patients (66.3%) had a Krauss index ≥0.5. Thirty-three patients (58%) were living independently after 2 years (mRS 0–2). The outcomes were worse for patients with multiple comorbidities. Neither an increased patient age nor a prolonged history of illness was statistically significant prognostic factors for adverse outcomes of VP-shunt surgery. Conclusion: Surgical treatment was well tolerated by patients with iNPH who received VP-shunts. Most patients experienced attenuation of their preoperative symptoms. Multiple concurrent comorbidities should be considered as adverse prognostic factors before shunt insertion in patients with iNPH.